Effects of Sowing Methods, Nitrogen and Seed Rates on Straw weight and Grain Yield of Acha (Digitaria exilis Kippis Stapf) at Naraguta Village, Jos, Plateau State - Dachi, S. N (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The Study was carried out at the experimental Research field of the Department of Crop Production, Naraguta Village, University of Jos during 2023 and 2024 cropping seasons to determine the appropriate sowing method, nitrogen and seed rates to step up the production of straw and grain of Acha for livestock and human use. The experimental design was a split- plot with three replications Nitrogen and seed rates were assigned to the main plot and sowing methods in the sub-plots. the treatments consisted of two sowing methods (broadcasting and drilling (at 50 cm inter-row spacing), three Nitrogen levels (0, 30 and 60 kg Nha-1) and three seed rates (10, 20 and 30kg ha-1) respectively. Each treatment was accommodated in a plot size of 4.0 m x 5. 0 m and alleyways of 0.5m and 1.0m were maintained between plots and replications respectively. The seeds were sown by broadcasting and drilling at 50cm inter- row spacing. The parameters measured were number of tillers, plant height, straw weights and grain yields. The results indicated that treatments had significant (P < 0.05) effect on all the parameters measured (number tillers, straw and grain yields) except plant height. Based on the results of the study, drilling method of sowing, nitrogen and seedings rates at 30kgha-1 and 60kg Nha-1 were optimum for straw production. While drilling method, nitrogen at 30kg Nha-1 and seeding rate also at 30kg ha-1 produced the highest grain yield over the remaining treatments.